Galectin-1-driven tolerogenic programs aggravate Yersinia enterocolitica infection by repressing antibacterial immunity - Davicino, Roberto Carlos (2017)
Yersinia enterocolitica is an enteropathogenic bacterium that causes gastrointestinal disorders, as well as extraintestinal manifestations. To subvert the host's immune response, Y. enterocolitica uses a type III secretion system consisting of an injectisome and effector proteins, called Yersinia outer proteins (Yops), that modulate activation, signaling, and survival of immune cells. In this article, we show that galectin-1 (Gal-1), an immunoregulatory lectin widely expressed in mucosal tissues, contributes to Y. enterocolitica pathogenicity by undermining protective antibacterial responses. We found higher expression of Gal-1 in the spleen and Peyer's patches of mice infected orogastrically with Y. enterocolitica serotype O:8 compared with noninfected hosts. This effect was prevented when mice were infected with Y. enterocolitica lacking YopP or YopH, two critical effectors involved in bacterial immune evasion. Consistent with a regulatory role for this lectin during Y. enterocolitica pathogenesis, mice lacking Gal-1 showed increased weight and survival, lower bacterial load, and attenuated intestinal pathology compared with wild-type mice. These protective effects involved modulation of NF-kB activation, TNF production, and NO synthesis in mucosal tissue and macrophages, as well as systemic dysregulation of IL-17 and IFN-γ responses. In vivo neutralization of these proinflammatory cytokines impaired bacterial clearance and eliminated host protection conferred by Gal-1 deficiency. Finally, supplementation of recombinant Gal-1 in mice lacking Gal-1 or treatment of wild-type mice with a neutralizing anti-Gal-1 mAb confirmed the immune inhibitory role of this endogenous lectin during Y. enterocolitica infection. Thus, targeting Gal-1-glycan interactions may contribute to reinforce antibacterial responses by reprogramming innate and adaptive immune mechanisms.